2006
DOI: 10.1021/ja063545n
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning the Production of Nanosized β-Carotene Particles Using Spinning Disk Processing

Abstract: Nanoparticles of trans-beta-carotene are accessible using spinning disk processing (SDP), by varying the reaction conditions and the choice of surfactant, macrocyclic amphiphiles, sulfonato-calix[4,5,6,8]arenes, and alpha,beta-cyclodextrins. SDP ensures rapid mixing and fast kinetics, and nanoparticles of the carotene formed in the presence of the calixarenes are stable with respect to extraction of the carotene into an organic solvent, unlike in the presence of the cyclodextrins. Insight into the supramolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Compound 1 indeed assembles into nanorafts using process intensification rotating surface (PIRS) technology, and into continuous structures based on bilayer arrangements, some of which are persistent in the gas phase. It is noteworthy that PIRS is a new method for fabricating nano-particles for which spinning disc processing (SDP) is rapidly developing; [10][11][12] the key components of SDP include a rotating disc with controllable speed, and feed jets located slightly off-center from the disc. SDP generates a thin fluid film (1-200 mm) on a rapidly rotating disc surface (300-3000 rpm), within which nano-arrays form (Figure 1), [12] with strong shearing forces creating turbulence and breaking the surface tension of the film, making waves and ripples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 indeed assembles into nanorafts using process intensification rotating surface (PIRS) technology, and into continuous structures based on bilayer arrangements, some of which are persistent in the gas phase. It is noteworthy that PIRS is a new method for fabricating nano-particles for which spinning disc processing (SDP) is rapidly developing; [10][11][12] the key components of SDP include a rotating disc with controllable speed, and feed jets located slightly off-center from the disc. SDP generates a thin fluid film (1-200 mm) on a rapidly rotating disc surface (300-3000 rpm), within which nano-arrays form (Figure 1), [12] with strong shearing forces creating turbulence and breaking the surface tension of the film, making waves and ripples.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that PIRS is a new method for fabricating nano-particles for which spinning disc processing (SDP) is rapidly developing; [10][11][12] the key components of SDP include a rotating disc with controllable speed, and feed jets located slightly off-center from the disc. SDP generates a thin fluid film (1-200 mm) on a rapidly rotating disc surface (300-3000 rpm), within which nano-arrays form (Figure 1), [12] with strong shearing forces creating turbulence and breaking the surface tension of the film, making waves and ripples. [11] These waves and ripples add to the vigor of mixing and ensure extremely short reaction residence time under plug flow conditions, with even mixing throughout the entire film.…”
Section: Introductionmentioning
confidence: 99%
“…3) Cyclodextrins (CyDs), cyclic oligosaccharides, are able to form inclusion complexes with hydrophobic drugs, improving their water solubility, stability and bioavailability. 4,5) CyDs can also form inclusion complexes with a number of isoprenoid compounds, such as CoQ10, [6][7][8][9] vitamin A, D, E, K, [10][11][12] β-carotene, 13) lycopene, 14) and teprenone, 15) and then improve their water solubility, stability and bioavailability. Likewise, Uekama and colleagues reported that 2,6-di-O-methyl-β-CyD (DM-β-CyD) or γ-CyD markedly improves solubility and oral bioavailability of CoQ10 in rats, dogs or humans.…”
Section: Improvement Of Pharmaceutical Properties Of Isoprenoid Compomentioning
confidence: 99%
“…More recently the HiGee reactor (cf. Figure 4) and also SDR28, 29 have been employed. The synthesis of BaSO 4 via precipitation (Reaction 5) is complete in a timescale of milliseconds and we thus took it as an example to study the suitability of an SDR as a precipitation reactor.…”
Section: The Preparation Of Small Particles With An Sdrmentioning
confidence: 99%